Persistence of lower dimensional invariant tori in a class of reversible systems. Issue 1 (2nd January 2018) - Hong, Weiwei; Zhang, Dongfeng
ABSTRACT: In this paper we prove the persistence of lower dimensional invariant tori for a class of reversible systems without any non-degeneracy condition. In the proof, we use the special nature that the dimension of the frequency ω is 2 and the modified KAM iteration to prove the persistence of lower dimensional hyperbolic invariant tori, but the frequency has some small shifts from small perturbations.